Relative aggressiveness of new virulences of Tilletia foetida and T. caries on wheat cultivars - and B.M. SINGH, R.S. CHAUHAN, A.K. SOOD (Indian Phytopathology, 2002)
Four new virulences of Tilletia [oetida (L-C, L-D, L-E and L-F) and two of T. caries (T-A and T-B) were identified on the basis of reaction on ten monogenic bunt differentials (Bt1 - Bt/O) of eight populations of both the pathogens collected from hill bunt prone areas of Himachal Pradesh. All these virulences constituted new combinations not described previously. Majority of the isolates were collectively virulent on B12, Br5, Bt7, B18, Bt9 and Bt l O differentials. Individual virulences varied in their ability to attack one to five genes for resistance. All the virulences were equally aggressive on wheat cultivars.